2018
DOI: 10.1017/s0033291717003464
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cognitive plasticity and goal-directed control in adolescent obsessive–compulsive disorder

Abstract: BackgroundYouths with obsessive–compulsive disorder (OCD) experience severe distress and impaired functioning at school and at home. Critical cognitive domains for daily functioning and academic success are learning, memory, cognitive flexibility and goal-directed behavioural control. Performance in these important domains among teenagers with OCD was therefore investigated in this study.MethodsA total of 36 youths with OCD and 36 healthy comparison subjects completed two memory tasks: Pattern Recognition Memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 57 publications
7
35
0
Order By: Relevance
“…Together with our data, these findings suggest that more work is warranted investigating vmPFC contributions to OCD symptoms in the context of flexible learning. Interestingly, reversal-learning performance deficits have been inconsistent in studies of OCD patients [11,12,32,33]; our findings suggest that these inconsistencies may reflect heterogeneity in neuropathology between study subject populations. OFC dysfunction has been demonstrated in OCD patients during reversal learning independent of reversal performance [11,12]; however, well-powered clinical studies with baseline and reversal-learningrelated neuroimaging data have not been performed to address whether heterogeneous task performance is associated with distinct neural correlates.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Together with our data, these findings suggest that more work is warranted investigating vmPFC contributions to OCD symptoms in the context of flexible learning. Interestingly, reversal-learning performance deficits have been inconsistent in studies of OCD patients [11,12,32,33]; our findings suggest that these inconsistencies may reflect heterogeneity in neuropathology between study subject populations. OFC dysfunction has been demonstrated in OCD patients during reversal learning independent of reversal performance [11,12]; however, well-powered clinical studies with baseline and reversal-learningrelated neuroimaging data have not been performed to address whether heterogeneous task performance is associated with distinct neural correlates.…”
Section: Discussionmentioning
confidence: 57%
“…The goal of this study was to determine whether Sapap3-KOs show OCD-relevant cognitive impairment, and assess functioning of associated PFC and striatal areas. OCD patients reliably show performance deficits and/or altered blood oxygen leveldependent (BOLD) responses during reversal-learning paradigms [11,12,32,33], and impaired reversal learning may reflect circuit dysfunction that could contribute to perseverative thoughts and actions [33]. We therefore used a reversal-learning paradigm to examine cognitive flexibility in Sapap3-KOs and wild-type (WT) littermates, and quantitative cFos analysis to determine if activity in PFC and striatal regions was differentially associated with reversal performance in Sapap3-KOs.…”
Section: Introductionmentioning
confidence: 99%
“…The 11 pediatric OCD studies included in the latter meta‐analysis had small samples ( n = <35 per group) and inadequate power to detect some differences, limiting conclusions. With respect to specific pediatric OCD case–control studies (Table ), significant performance differences have been reported, albeit inconsistently, in planning, cognitive flexibility, verbal working memory, nonverbal memory, visual‐spatial ability, and processing speed (Andrés et al, ; Gottwald et al, ; Ornstein, Arnold, Manassis, Mendlowitz, & Schachar, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is largely consistent with prior work: previous studies of Gillan and colleagues ( Gillan et al, 2015 , Gillan et al, 2014 , Gillan et al, 2011 ) recruited older participants (mean age: ~37–43) than were tested in the present study. A study of adolescents with OCD obtained evidence of impairment of goal-directed behavior ( Gottwald et al, 2018 ), although this was primarily through a slips of action test and differential outcome learning. Thus, across the present study and prior work, the age of the participants, and the duration of OCD illness, may be an important determinant of devaluation performance, and might explain discrepancies across studies.…”
Section: Discussionmentioning
confidence: 99%